Pengujian Statis pada Sistem Server Web Berbasis Cluster dengan Algoritme Never Queue - Nongki Angsar (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2018)
The increase of web traffic and the development of network bandwidth are relatively faster than the development of microprocessor technology. This causes one point server platform no longer adequate to meet the needs of system scalability web server. Thus, multiple server platforms are the answer. One solution that has been known is a cluster-based web server system. This paper designs and develops cluster based web server system with Never Queue Algorithm. The system is then tested with a web workload distribution testing. The testing iscarried out by generating HTTP workloads statically (with fixed HTTP request rate) from the client to a web server system pool. The result shows that HTTP requests are well-distributed to web server system pool by Never Queue Algorithm. HTTP reply rate tends to be stable at average of 1,031.8 replies/s because the system is saturated, while TCP connection rate, response time, and error, tend to rise along with the rise of HTTP request rate. As for throughput, the average is 2.983 Mbps. Correlation between stability and the rise of error is, at the saturated point, bigger HTTP requests yield bigger errors.